Employee Work Professionalism in Service Public (Case Study in Kayubulan Village, Limboto District) - Rusly Abdurahman Idji; Harijono H. Imbran; Nabila Shanaz Sukaina Holle (Journal of Management and Administration Provision, 2021)
This research was conducted in Kayubulan Sub-District, Limboto District, Gorontalo Regency. This study aims to determine how the Professional Work of Employees in Public Services (Case Study in Kelurahan Kayubulan, Limboto District. The research method uses descriptive qualitative type using data sourced from interviews with predetermined informants, each Camat, Lurah, Kelurahan Secretary, 2 Section Heads, 1 staff member and 2 community members. The results of the study concluded that the staff of the Subdistrict of Keyubulan, Limboto District had shown quite good, although it was still not optimal. This is seen from four aspects of professionalism, namely; aspects of Equality, aspects of equity, loyalty, and accountability. These four aspects have been able to be demonstrated quite well by employees in Kayubulan Sub-District, Limboto District. In conducting public services.